2013
DOI: 10.3109/09553002.2013.767992
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced cellular radiosensitivity induced by cofilin-1 over-expression is associated with reduced DNA repair capacity

Abstract: Purpose-A previous report has indicated that over-expression of cofilin-1 (CFL-1), a member of the actin depolymerizing factor (ADF)/cofilin protein family, enhances cellular radiosensitivity. This study explores, the involvement of various DNA damage responses and repair systems in the enhanced cellular radiosensitivity as well as assessing the role of CFL-1 phosphorylation in radiosensitivity.Materials and Methods-Human non-small lung cancer H1299 cells harboring a tet-on gene expression system were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…In order to further determine the role of cofilin-1 in THC-induced anti-inflammation in the MG-63 cells, we used doxycycline, which can upregulate the expression of cofilin-1 significantly in vitro [ 20 , 21 ]. We observed that 0.1 μ g/mL doxycycline markedly increased the expression of cofilin-1 in MG-63 cells ( Figure 6(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further determine the role of cofilin-1 in THC-induced anti-inflammation in the MG-63 cells, we used doxycycline, which can upregulate the expression of cofilin-1 significantly in vitro [ 20 , 21 ]. We observed that 0.1 μ g/mL doxycycline markedly increased the expression of cofilin-1 in MG-63 cells ( Figure 6(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…This recommended that CKB knockdown reduced cytosolic glycolysis and resulted in a tumor suppressive metabolic state in Skov3 cells [29] . Cofilin1 (CFL-1) over-expression enhances radiosensitivity and is associated with reduced DNA repair capacity [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Private Practice, Mechanicsville, VA, USA Sir : I read with great interest the recent article by Leu et al (2013) concerning the role of cofi lin-1 in cell radiosensitivity. It is interesting to note that cofi lin-1 may also play a major role in tumor growth and progression in a number of systemic malignancies.…”
Section: Shailendra Kapoormentioning
confidence: 99%